Medical Machines: The Expanding Role of Ethics in Technology-Driven Healthcare - Brenna, Connor (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2021)
Emerging technologies such as artificial intelligence are actively revolutionizing the healthcare industry. While there is widespread concern that these advances will displace human practitioners within the healthcare sector, there are several tasks – including original and nuanced ethical decision making – that they cannot replace. Further, the implementation of artificial intelligence in clinical practice can be anticipated to drive the production of novel ethical tensions surrounding its use, even while eliminating some of the technical tasks which currently compete with ethical deliberation for clinicians’ limited time. A new argument therefore arises to suggest that although these disruptive technologies will change the face of medicine, they may also foster a revival of several fundamental components inherent to the role of healthcare professionals, chiefly, the principal activities of moral philosophy. Accordingly, “machine medicine” presents a vital opportunity to reinvigorate the field of bioethics, rather than withdraw from it.